Eksplorasi Konsep Pembinaan Masyarakat Islam melalui Tradisi khataman Al-Quran di Masjid Agung Lamongan dan Masjid Namira - Ulya, Musrifatul (Maddah: Journal of Advanced Da'wah Management Research, 2023)
The Quran is the holy book of Islam, making it of paramount importance in the global Muslim faith. Memorization and comprehension of the Quran are significant traditions, such as the khataman. Gratitude rituals, like "Muggahan," in East Java are also emphasized, merging religious elements with the local culture. Islamic culture exerts a strong influence in East Java, despite the presence of other religions. Consequently, exploring the concept of fostering the Islamic community through the tradition of khataman Al-Qur'an is deemed essential in harmonizing local customs with Islamic values. This tradition enriches not only individual spirituality but also strengthens social bonds within the Muslim community. The research primarily addresses the following questions: 1) How can the concept of fostering the Islamic community be explored? 2) How can the khataman tradition be optimized in fostering the Islamic community? This research employs qualitative research methods and is conducted at the Masjid Agung Lamongan and Masjid Namira. The study's findings reveal that the concept of fostering the Islamic community through the khataman Al-Qur'an tradition can be explored from various aspects: 1) the spiritual aspect, 2) the intellectual aspect, and 3) the social aspect. The optimization of the khataman tradition in fostering the Islamic community involves: 1) Raising awareness among the community about the significance of the khataman Al-Qur'an tradition, 2) Developing engaging and innovative Quranic memorization programs, and 3) Enhancing the facilities and resources to support the execution of the khataman Al-Qur'an tradition.